2015
DOI: 10.1097/bsd.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Complete Lateral Dislocation at the Lumbosacral Junction

Abstract: A combined anterior and posterior arthrodesis with decompression and instrumentation is an effective method for the treatment of this type of lumbosacral dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The sequential evaluation and use of multi-modality imaging modalities help diagnose these complex injuries [5]. Recent literature reports that a majority of these injuries result in an anterior dissociation of the lumbosacral joint, with posterior dissociation and lateral dissociation being among the least common [4,[12][13][14][15]. The management of TLSD is typically a complex and multifactorial effort because of the multisystem involvement including injury to major vessels and abdominal and spinal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The sequential evaluation and use of multi-modality imaging modalities help diagnose these complex injuries [5]. Recent literature reports that a majority of these injuries result in an anterior dissociation of the lumbosacral joint, with posterior dissociation and lateral dissociation being among the least common [4,[12][13][14][15]. The management of TLSD is typically a complex and multifactorial effort because of the multisystem involvement including injury to major vessels and abdominal and spinal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al reported that 10% of reported lumbosacral fracture dislocations were not initially recognized, though these were in patients where X-ray was the primary imaging modality [ 36 ]. Clinical presentation varies widely, [ 59 78 ] and may include severe lower back pain with exam findings such as flank hematomas, abrasions or palpable step-offs of the spinous processes.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Aihara et al reported a 68.4% rate of neurologic deficit in 57 cases [ 1 ], while only 3 out of 11 patients (27.3%) in the series by Vialle et al demonstrated neurological injury [ 58 ]. Grivas et al reported a 58% rate of neurologic deficit for all lumbosacral fracture dislocations [ 2 ], while Arandi et al found an 89% rate of neurological injury for complete lumbosacral dislocations [ 59 ].…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 2 more Smart Citations